(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Plywood manufacturing is one of the most important production lines and value adding alternatives in woodworking industry. Plywood production volumes have increased rapidly in the last few years all over the world and especially in Asian countries. In this new environment the European manufacturers face a great competition. In these market conditions the manufacturing companies can either do better, extracting the best they can and providing much greater quality, or go down to slow and painful market dropout. Bulgaria is on the crossroad- to improve its plywood production in terms of investments and quality, or let its manufacturers in stagnation, waiting until their doors get closed. All these facts define strategic analyses that can outline the future improvement of Bulgarian plywood production as a question of present interest for the woodworking industry.